Carotid Artery Stenosis - Edward Y Woo (Radcliffe Medical Media, 2019)
Stroke is one of the leading causes of death in the world and carotid artery stenosis is a major cause of ischaemic strokes. Symptomatic patients are often treated with either carotid endarterectomy (CEA) or carotid artery stenting (CAS). Asymptomatic patients can be treated with best medical therapy, CEA or CAS. While guidelines exist for the management of carotid artery stenosis, the results of recent studies are controversial regarding the safety of CAS compared with CEA. This review aims to outline the current guidelines while reviewing up-to- date studies and analyses. Future studies and emerging technologies are outlined in an attempt to provide an evaluation of the current data and management of this complex problem.